Effects of Different Primary Processing Methods on the Flavor of Coffea arabica Beans by Metabolomics - Xiaojing Shen; Chengting Zi; Yuanjun Yang; Qi Wang; Zhenlai Zhang; Junwen Shao; Pincai Zhao; Kunyi Liu; Xingyu Li; Jiangping Fan (Fermentation, 2023)
The primary processing method of coffee plays a crucial role in determining its flavor profile. In this study, roasted coffee beans were subjected to three primary processing methods, i.e., natural processing (SC), washed processing (WC), and honey processing (MC), that were analyzed by LC-MS/MS and GC-MS metabolomics. Additionally, sensory evaluation was conducted by the Specialty Coffee Association of America (SCAA) to assess coffee flavor characteristics. The results showed that 2642 non-volatile compounds and 176 volatile compounds were detected across the three primary processing methods. Furthermore, significant differentially changed non-volatile compounds (DCnVCs) and volatile compounds (DCVCs) were detected among SC/WC (137 non-volatile compounds; 32 volatile compounds), MC/SC (103 non-volatile compounds; 25 volatile compounds), and MC/WC (20 non-volatile compounds; 9 volatile compounds). Notable compounds, such as lichenin, 6-gingerdiol 5-acetate, 3-fluoro-2-hydroxyquinoline, and 4-(4-butyl-2,5-dioxo-3-methyl-3-phenyl-1-pyrrolidiny)benzenesulfonamide, were identified as important DCnVCs, while ethyl alpha-D-glucopyranoside, 2,3-butanediol, maltol, and pentane-1,2,5-triol were identified as significant DCVCs in SC/WC. In MC/SC, 3-fluoro-2-hydroxyquinoline, etimicin, lichenin, and imazamox were important DCnVCs, whereas ethyl alpha-D-glucopyranoside, 2-pyrrolidinone, furfuryl alcohol, and pentane-1,2,5-triol were import DCVCs. Lastly, MC/WC samples exhibited notable DCnVCS, such as (S)-2-hydroxy-2-phenylacetonitrile O-[b-D-apiosyl-1->2]-b-D-glucoside], CMP-2-aminoethyphosphonate, talipexole, and neoconvallatoxoloside, along with DCVCS including citric acid, mannonic acid, gamma-lactone, 3-(1-hydroxy-1-methylethyl)benzonitrile, and maltol. Therefore, the primary processing method was a useful influence factor for coffee compositions.